Heavy Metals Excessive Intake in Humans: Implications for Brain Cognition and Selected Dietary Essential Micronutrients - SARKINGOBIR, YUSUF; AMINU UMAR IMAM (Universitas Hang Tuah, 2024)
The objective of this article is to deliver a conceptual review of implications of heavy metals intake for brains and certain dietary nutrients such as copper, zinc, etc. Heavy metals are metallic or relative elements that are described bases on certain characteristics such as higher density, toxicity, and likes. They are present ideally in the natural environment, therefore, have to be expunged through human activities which are currently excessive in nature. Humans take in heavy metals because of excessiveness of human activities and thereby causing detrimental effects on the body, brain, development, and nutritional growth. On the brain, heavy metals improvised ways to circumvent the wall of the bilayer and exert harm on certain areas of the brain. This lead to poor functioning of the brain, as well as the body. Similarly, the heavy metals utilized efforts such as molecular mimicry or chelation to outcompete or impede the functions of essential micronutrients required for body functioning. Cd2+ impede Cu2+, Ca2+, and Zn2+; Pb2+ also has the ability to impede essential elements. Other heavy metals such as chromium, arsenic, exert similar approaches. This review elucidated the following themes: Meaning of heavy metals, dietary sources of heavy metals, non-dietary sources of heavy metals, dietary nutrients for learning/cognition, implications of heavy metals to the Brian or quasi, effects of heavy metals on micronutrients. Food materials, and water should be safeguarded from heavy metals through disparate methods. Curative methods for heavy metals removal (remediation) should be made accessible to all.